Malaria during pregnancy and newborn outcome in an unstable transmission area in Brazil: A population-based record linkage study. - Jamille Gregório Dombrowski; Rodrigo Medeiros de Souza; Natércia Regina Mendes Silva; André Barateiro; Sabrina Epiphanio; Lígia Antunes Gonçalves; Claudio Romero Farias Marinho (PLoS ONE, 2018)
Background Malaria in pregnancy (MiP) is one of the major causes of mortality and morbidity in tropical regions, causing maternal anemia, intrauterine growth retardation, preterm birth, and low birth weight (LBW). The integration of the information systems on pregnancy and malaria could prove to be a useful method of improved decision making for better maternal-child health. Methods A population-based observational study acquired information retrospectively from all live births that occurred between 2006 and 2014 in Cruzeiro do Sul (Acre, Brazil). Social and clinical data of the mother and newborn was extracted from the Information System of Live Births. Malaria episodes information was obtained from the Brazilian Epidemiological Surveillance Information System Malaria. A deterministic record linkage was performed to assess malaria impact on pregnancy. Results The studied population presented a malaria incidence of 8.9% (1283 pregnant women infected), of which 63.9% infected by Plasmodium (P.) vivax. Reduction of newborn birth weight at term (small for gestational age (SGA) and LBW) has been found associated with P. vivax infection during pregnancy (SGA-OR 1.24, 95% CI 1.02-1.52, p = 0.035; term LBW-OR 1.39, 95% CI 1.03-1.88, p = 0.033). Additionally, P. falciparum infection during pregnancy has been found to be associated with preterm births (OR 1.54, 95% CI 1.09-2.18, p = 0.016), which is related with late preterm births (OR 1.59, 95% CI 1.11-2.27, p = 0.011). Conclusions Despite the decrease of malaria cases during the evaluation period and regardless of Plasmodium species, we present evidence of the deleterious effects of MiP in a low transmission area in the Amazonian region.